Active Polite Expression study Frozen II Movie - Sri Fajar Ayu (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
The purpose of study was described the polite expression of assertive speech act on the video movie of Frozen II using Brown and Levinson’s politeness theory. As well as the implication for learning polite expression. The method used a qualitative using the consideration that this study mainly aims at findings the most dominant type of politeness expression in Frozen II Movie. The result of study used of assertive speech acts include stating, suggesting, bragging, and complaining. Polite expression used by the characters is positive polite including Attend to h’s interest, need and wants has 9 utterances, use solidarity in group has 1 utterances, be optimistic has 10 utterances, include both speaker and hearer in activity has 4 utterances, offer or promise has 4 utterances, avoid disagreement has 4 utterances, joke has 1 utterances. The most used find in positive polite is be optimistic. This also shows that in saying a sentence what is sought is not who is most polite, but a person’s ability to defend themselves build optimistic and positive thinking. The implication of this research is the use of politeness types to anyone who wants to speak more politely. Keywords: Polite expression, types, positive polite, Frozen II movie